Purification and crystal structure of human ODA16: Implications for ciliary import of outer dynein arms by the intraflagellar transport machinery. (20th April 2020) - Wang, Jiaolong; Taschner, Michael; Petriman, Narcis A.; Andersen, Marie B.; Basquin, Jerome; Bhogaraju, Sagar; Vetter, Melanie; Wachter, Stefanie; Lorentzen, Anna; Lorentzen, Esben
Abstract: Motile cilia protrude from cell surfaces and are necessary to create movement of cells and fluids in the body. At the molecular level, cilia contain several dynein molecular motor complexes including outer dynein arms (ODAs) that are attached periodically to the ciliary axoneme, where they hydrolyse ATP to create the force required for bending and motility of the cilium. ODAs are preassembled in the cytoplasm and subsequently trafficked into the cilium by the intraflagellar transport (IFT) system. In the case of the green alga Chlamydomonas reinhardtii, the adaptor protein ODA16 binds to ODAs and directly to the IFT complex component IFT46 to facilitate the ciliary import of ODAs. Here, we purified recombinant human IFT46 and ODA16, determined the high‐resolution crystal structure of the ODA16 protein, and carried out direct interaction studies of IFT46 and ODA16. The human ODA16 C‐terminal 320 residues adopt the fold of an eight‐bladed β‐propeller with high overall structural similarity to the Chlamydomonas ODA16. However, the small 80 residue N‐terminal domain, which in Chlamydomonas ODA16 is located on top of the β‐propeller and is required to form the binding cleft for IFT46, has no visible electron density in case of the human ODA16 structure. Furthermore, size exclusion chromatography and pull‐down experiments failed to detect a direct interaction between human ODA16 and IFT46. These data suggest that additional factors may be required for the ciliary import of ODAs in human cells with motile cilia.